Storytelling Method of Instruction, School Location and Students’ Academic Achievement: Any Synergy? - Ayodeji Francis Fasuba (Journal of Elementary and Secondary School, 2024)
Stakeholders in the education industry in Ekiti State have criticized the unsatisfactory performance of CRS students’ results in external examinations in rural schools. This study examined storytelling methods of teaching, school locations, and students’ academic achievement in Christian Religious Studies (CRS) in Senior Secondary Schools, Ekiti State, South West Nigeria. Research questions and hypotheses were developed for the study. The design adopted for the study was a quasi-experimental research of two groups, that is, one experimental group and one control group. The Senior Secondary School Two (SSS2) students of the Ekiti State public secondary schools formed the population. The schools (rural and urban) for the study were purposively selected from Ekiti South-West Local Government Area of Ekiti State. A total of 159 students participated as the sample for the study. One instrument, ‘Achievement in CRS’ (ATCRS) instrument was used for data collection. The research hypothesis was analyzed using analysis of Variance (ANOVA). Findings from the study revealed no significant difference in the academic achievement of urban and rural students with CRS utilizing storytelling and conventional lecture methods. The study concludes that storytelling is a location friendly teaching method. The recommendations are based on the finding that teachers of CRS in Ekiti State public secondary schools should adopt the storytelling method during the instructional process to enhance students’ academic achievement in both rural and urban schools.